A critical study on status of subsidy on seeds and fertilizer and its co-relation with marketing in India - Tripathi, Santosh Kumar (International journal of economic perspectives, 2008)
During now Asian country was heavily dependent upon foreign food aid that compromised India’s sovereignty over crucial matters. It had been at now accomplished that, excluding building structure for storage and distribution, self-direction in production of food grains is imperative. It resulted in large investments in agriculture productivity, through the means that of hybrid seeds, Chemical Fertilizers, Pesticides and irrigation infrastructure. This came to called revolution. Agriculture sector is without doubt most vital sector of Indian economy because it provides employment to fifty four. 6% of individuals and food security of Asian nation revolves around this sector. Its importance are often gauged by the actual fact that whenever there's concern of deficit monsoon, whole of the population starting from farmers, workers, businessmen, policy manufacturers and even foreign investors are caught into nervousness. Owing to dependence of disproportionate population on this sector, Indian economy are often still aforementioned to be associate rural economy. However, sector is basically state controlled that resulted in widespread inefficiencies and distortions. The marketing strategies of the companies largely affected by the subsidies given by the the authorities. This paper analyses the status of the subsidy and also co-relate this with the marketing of seeds and fertilizers.